Comparative study between Ni/MgO and Ni/MgO-ZrO2 as catalyst for the dry reforming of methane - Monroy, Teddy G. (Animo Repository, 2009)
Methane dry reforming is one of the important routes in converting greenhouse gases methane and carbon dioxide into syngas that can later be used as feedstock for the processing of other useful chemicals such as methanol and oxygenated chemicals. This process uses catalysis, often nickel-based, to increase the reaction rate. To date, the dry reforming of methane has limited commercial application due to the rapid deactivation of the catalysis. Both reactants contain carbon species that has a high potential of blocking active sites on the surface of the catalysts, thus, deactivating them. Past researches have shown that the type of support material is critical in controlling the amount of carbon deposited on the surface of the catalyst during methane dry reforming. A support material that is predominantly basic is preferred since it discourages the formation of inactive carbon deposits. Support materials that can easily provide mobile oxygen species can likewise deter catalyst deactivation. This study focuses investigating 15% Ni/MgO-ZrO2 as a catalyst for methane dry reforming and compares it with commonly used catalysts such as Ni/MgO. Catalysts were prepared using the impregnation method, calcined at 8500C, and reduced under a stream of 80/20 He/H2 at 5000C. Catalyst characterization using advanced instrumentation such as the AAS, BET, XRD, and TPD were also conducted.